La interculturalidad en la enseñanza del español como lengua extranjera en la pasantía de la práctica profesional - Gileno, Rosangela Sanches da Silveira [UNESP]; Rocha, Nildiceia Aparecida [UNESP] (My University, 2014)
In the contemporary literature on Foreign Language Teaching (LE/L2), is evidence of a trend in education given priority from the sub-focus on socio-cultural competence (HYMES, 1972), mainly with the aim of developing the intercultural competence, that is, the power to know the differences between the culture of the new language and the language in concrete situations and to develop strategies to deal comprehensively with the customs of another culture (Rozenfeld & Vianna, 2011). This process seeks to bring people to a critical analysis of their own language and culture, the concept of otherness and the similarities and differences between nations (MOTTA ROTH, 2003). Under the didactic-pedagogical approach multiculturalism, there is the need to develop new educational proposals and to include studies and researches about this subject in the curricula of teacher education courses. Politically, the proposals of the "Parâmetros Curriculares Nacionais (PCNs)" in Brazil emphasize as targets to be established for the teaching of Spanish as a foreign language (ELE), on average, target content and teaching strategies to develop, in addition to communicative competence, competition also "inter (multi) culture" (BRASIL, 2000). Thus, this paper analyzes the reports of pre-service teachers in the course of Teaching Practice of Spanish Language, the presence of cultural and intercultural approach, verifying didactic-pedagogical treatment that is being expressed in projects and materialized in practices of ELE classroom, in the interior of São Paulo / Brazil.

En la literatura contemporánea sobre didáctica de Lengua Extranjera (LE/L2), se evidencia una tendencia en privilegiarse la enseñanza a partir del enfoque en la sub-competencia socio-cultural (HYMES, 1972), principalmente, con el objetivo de desarrollar en el aprendiz la competencia intercultural, o sea, la competencia para conocer las diferencias entre la cultura de la nueva lengua y la lengua propia en situaciones concretas y para desenvolver estrategias para lidiar de forma comprensiva con las costumbres de la otra cultura (ROZENFELD; VIANNA, 2011). Ese proceso busca llevar el individuo a un análisis crítico de su propia lengua y cultura, de la concepción de alteridad y de las semejanzas y diferencias entre naciones (MOTTA ROTH, 2003). Bajo el enfoque didáctico-pedagógico en la interculturalidad, surge la necesidad de desarrollar nuevas propuestas didácticas y de incluir en los currículos de formación de profesores, cursos e investigaciones en esta área. Políticamente, las propuestas de los “Parâmetros Curriculares Nacionais” en Brasil enfatizan como objetivos a ser establecidos para la enseñanza de Lengua Española como lengua extranjera (ELE), en nivel medio, focalizar contenidos y estrategias didácticas que desarrollen, además de la competencia comunicativa, también la competencia “inter(pluri)cultural.” (BRASIL, 2000). Así, esta comunicación analiza en los informes de las pasantías en la asignatura de Práctica de la Enseñanza de la Carrera de LetrasEspañol, la presencia del enfoque cultural e intercultural, verificando el tratamiento didáctico-pedagógico que está siendo plasmado en proyectos y materializados en prácticas de sala de clase de ELE, en el interior del estado de São Paulo/Brasil.
The intercultural approach in teaching Spanish as a foreign language in professional practices
Keywords: Interculturalism; Spanish as a foreign language; Teaching practices; Interculturalidad; Español como lengua extranjera; Pasantía docente